Role of neuropeptide Y in development of valproate-induced eating behaviour disorder - N. A. Shnayder; V. V. Grechkina; M. Ya. Kissin; D. V. Dmitrenko; R. F. Nasyrova (Эпилепсия и пароксизмальные состояния)
Background. Eating behaviour disorder (EBD) induced by valproic acid (VPA) is one of the components of the pathogenesis of a serious complication of therapy with VPA and its salts such as VPA-induced metabolic syndrome (MetS). About 20% of patients receiving VPA have weight gain, which is also a consequence of altered eating behaviour in such patients. Substances such as neuropeptide Y (NPY), leptin, orexin and ghrelin are involved in the regulation of eating behaviour. NPY has received special attention in recent years because it is one of the most potent brain orexigenic peptides and its expression level directly affects the quantity and quality of food intake. NPY overexpression is associated with EBD, food preferences, obesity, and MetS.Objective: to review preclinical and clinical studies of NPY role as a potential sensitive and specific serum biomarker of VPA-EBD, secondary weight gain and VPA-MetS development in children and adults with epilepsy.Material and methods. We analyzed Russian and foreign publications submitted to eLibrary, PubMed/MEDLINE, Scopus, and Google Scholar databases between 2014 and 2024. The full-text articles in Russian and English (original studies, systematic reviews, meta-analyses, Cochrane reviews, and clinical cases) were analyzed. After the selection procedure, 53 out of 1105 publications retrieved by query keywords were included in the analysis.Results. VPA-EDB refers to multifactorial diseases, requiring to take into account the additive contribution of external (food education, eating habits of the patient and family members) and internal (key hormones and neuropeptides regulating appetite and food preferences, the dose and duration of VPA intake, the metabolic rate of VPA) factors while assessing a risk of its development. NPY-associated VPA-EDB affects dietary preferences in favor of high-calorie food and beverages, increases the frequency of meals, the risks of insulin resistance, hyperglycemia as one of the major domains in MetS pathogenesis.Conclusion. VPA-EBD requires timely diagnosis, as it can cause VPA-MetS. NPY is an important biomarker of VPA-EBD, because recent studies have convincingly demonstrated that this neuropeptide is involved in the regulation of eating behavior in patients with epilepsy.